Giant Malignant Peripheral Nerve Sheath Tumor of Scalp in Non-neurofibromatosis Person: A Rare Case Report - Gupta, Amit; Kumar, Rakesh; Ojha, Bal Krishna; Chandra, Anil (Indian Journal of Neurosurgery, 2018)
Malignant peripheral nerve sheath tumors (MPNSTs) are rare neoplasms, usually arising from components of nerve sheath such as perineural fibroblasts or Schwann cells. Primary scalp MPNST is an exceptionally rare entity and only few cases have been reported till date. We encountered an unusual case of giant scalp MPNST in a 70-year-old man without any history suggestive of neurofibromatosis associated with intracranial extension with underlying bone destruction. The tumor was treated with complete surgical excision followed by adjuvant radiotherapy. Histopathological examination showed hyper- and hypocellular areas of spindle cells admixed with myxoid areas and immunohistochemistry revealed positivity to vimentin and S100 on the basis of which the diagnosis of MPNST was made.
Keywords: malignant peripheral nerve sheath tumor; occipital; scalp; S100; surgical resection; radiotherapy